Encapsulation of Satureja khuzistanica jamzad essential oil in chitosan nanoparticles with enhanced antibacterial and anticancer activities. Issue 10 (2nd November 2021) - Rashidipour, Marzieh; Ashrafi, Behnam; Nikbakht, Mohammad Reza; Veiskarami, Saeed; Taherikalani, Morovat; Soroush, Setareh
Abstract: Satureja khuzistanica jamzad (SKJ), which is a member of Lamiaceae, has various proven effects such as antispasmodic and anti-inflammatory, anti-diabetic, antioxidant, and antifungal properties. However, the use of essential oil of plants is limited due to their inherent instability in the environment. Encapsulation with nanoparticles in the nanogel forms is one of their stabilization methods. The aim of this study was to synthesize nano-gel based on chitosan (CS) and extracts of SKJ essential oil, and to evaluate the antibacterial and anticancer activities. SKJ essential oil was extracted using water distillation method. Then, it was loaded on CS particles using two-step process as following: droplets formation and freezing. The Dynamic Light Scattering (DLS), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), and Zeta potential determination were used to evaluate the physical and chemical properties of CS-SKJ nanogel, which its result was acceptable. After confirmation of the loaded essential oil rate and releasing amount, the antibacterial effects were evaluated on five Gram-positive bacteria and five Gram-negative bacteria using microbroth dilution method. The encapsulation efficiency, size, polydispersity index, and zeta potential of nanoparticles were characterized were 30.74%, 571.00 nm, 0.451 and −67.2 mV, respectively. The results were significant not only on Gram-positive bacteria, but also on Gram-negative bacteria. The MIC range was between 7.8 and 500 µg/ml. The CS-SKJ nanogel has acceptable anticancer activities on KB and A549 tumor cell lines. the IC50 range was between 5.6 and 6.71 µg/ml. The results indicate that both CS particles and SKJ alone, and CS-SKJ nanogel could be considered as the outlook to produce new antimicrobial and anticancer drugs. Graphical Abstract: UF0001